Unkonventionelle massnahmen der geldpolitik: eine kritische Beurteilung. Non-coventional measures of momentary policy: a critical assesment - Rohde, Armin (Estonian Discussions on Economic Policy, 2014)
In the present article a recently observable very expansive monetary policy and especially the additional use of so called non-conventional measures of monetary policy is discussed in the case of the European Central Bank The goal of research is to analyse first to what extend the non-conventional measures of monetary policy are useful instruments to support the monetary policy of the Eurosystem, which is focusing more strictly on developments of interest rates and interest rate levels than on developments of the quantity of money since 2003/2004, when the ECB had changed its monetary policy strategy. Secondly the non-conventional measures, implemented by the ECB, are observed at the background of the institutional arrangements of the Eurosystems recent monetary policy, which is characterized in short by free and unlimited allotment of central bank money. So if there exist no shortage of central bank money within the banking system of the Eurosystem the question has to be analyzed why for example measures of Quantitative Easing should be necessary to make monetary policy more efficient. Afterwards the intensions of the ECB to use non-conventional measures are discussed in detail. This involves an intensive look on the sense of the intended return of actually very low interest rates to the aim of the ECB of maintaining inflation rates below, but close to 2%. Also a critical look is thrown on the background of the intended sizeable impact on the balance sheet of the Eurosystem by purchasing bonds or securities or by using targeted long term refinancing operations (TLTROs). And at least dangers of the implicitly intended depreciation of the Euro exchange rates are discussed. All in all these intensions of the ECB seems to be not the right way to lead to a proper solution of actually existing economic problems within the Eurozone.